Association of TLR4-T399I Polymorphism with Chronic Obstructive Pulmonary Disease in Smokers. (24th January 2010) - Speletas, Matthaios; Merentiti, Vassiliki; Kostikas, Konstantinos; Liadaki, Kyriaki; Minas, Markos; Gourgoulianis, Konstantinos; Germenis, Anastasios E.
Abstract : Tobacco smoking has been considered the most important risk factor for chronic obstructive pulmonary disease (COPD) development. However, not all smokers develop COPD and other environmental and genetic susceptibility factors underlie disease pathogenesis. Recent studies have indicated that the impairment of TLR signaling might play a crucial role in the development of emphysema. For this purpose we investigated the prevalence and any possible associations of common TLR polymorphisms (T L R 2 -R753Q, T L R 4 -D299G, andT L R 4 -T399I) in a group of 240 heavy smokers (>20 pack years), without overt atherosclerosis disease, of whom 136 had developed COPD and 104 had not. The presence ofT L R 4 -T399I polymorphism was associated with a 2.4-fold increased risk for COPD development (P = .044 ), but not with disease stage or frequency of exacerbations. Considering that infections contribute to COPD and emphysema pathogenesis, our findings possibly indicate that dysfunctional polymorphisms of innate immune genes can affect the development of COPD in smokers. Although this finding warrants further investigation, it highlights the importance of impaired innate immunity towards COPD development.